WHY ENGLISH MAJOR STUDENTS IN ACEH CHOOSE TO LEARN ENGLISH: AN IN-DEPTH INVESTIGATION INTO MOTIVATIONS - Mulyadi Syahputra (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This quantitative study investigates the motives prompting first-year students in Aceh, comprising 132 participants from English Department Students across different academic years in Bina Bangsa Getsempena University, to learn the English language. Utilizing the Attitude/Motivation Test Battery model, the research employs surveys to glean insights into the diverse motivations of 92 female and 40 male students. By applying established theories of language learning motivation, the study aims to discern the nuanced reasons underpinning students' decisions to engage with English. The findings, rooted in a robust quantitative methodology, not only enrich the empirical understanding of language learning motivations but also offer practical implications for refining language education strategies in the distinctive context of Aceh.